Composite concrete – Unregularized timber section for flat roof construction. (October 2020) - Mohammed, Azad A.; Mohammed, Othman K.
Abstract: At a global level, there is a vital need to reduce the demand on concrete, because this construction material harms the environment, mainly due to carbon dioxide emission and destroying the surrounding nature for the purpose of taking raw materials during Portland cement manufacturing. This study is an encouraging attempt to utilize the natural resources for the roof construction and diminish using of concrete. This study aimed at investigating the structural behavior and performance of composite concrete-unregularized timber beam. The system essentially consists of a relatively thin concrete section slab and populus nigra timber (PNT) joist. Essential tests on concrete and timber materials were conducted in the laboratory, in addition to five composite concrete-timber beams. Results show that there is a good chance to use the PNT joist for composite roof construction. The resulted composite section is well recognized by a high stiffness and high load carrying capacity. It was found that steel screw fasteners provided at 100 mm spacing is the best arrangement and can be safely used for connecting concrete to the unregularaized timber section. Further, there is a chance to use Eurocode 5 design proposal to check the stresses in both materials safely at serviceability and ultimate limit stages, because the PNT timber behaves elastically till failure without appreciable post ultimate response.